ANTIMICROBIAL ACTIVITY OF THREE MEDICINAL PLANTS (ARTEMISIA INDICA, MEDICAGO FALCATA AND TECOMA STANS) - Adnan, Muhammad; Adnan, Muhammad; Tariq, Akash; Akhtar, Basreen; Ullah, Riaz; AbdElsalam, Naser M. (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Artemisia indica, Medicago falcata and Tecoma stans are traditionally being use for medicinal purposes in Pakistan. Present study was designed to check in-vitro efficacy of these plants against selected bacterial and fungal strains.Methodology: Chloroform, butanol, ethyl acetate and n-hexane extracts of these plants were used for antimicrobial screening. Antibacterial activity was tested against four pathogenic bacterial strains i.e. Escherichia coli, Pseudomonas aeruginosa, Salmonella typhi and Staphylococcus aureus while antifungal activity was tested against four fungal strains i.e. Aspergillus flavus, Aspergillus niger, Aspergillus fumigatus and Fusarium solani.Results: Chloroform, butanol and ethyl acetate extracts of Artemisia indica, Medicago falcata and Tecoma stans showed high inhibitory activities (between 15-20 mm) against E. coli, P. aeruginosa and S. aureus. However, all extracts of Artemisia indica showed inhibitory activities (12-14 mm) against Salmonella typhi. As antifungal activities, the n-Hexane and chloroform extracts of Artemisia indica have completely inhibited the growth of Aspergillus flavus and Fusariun solani, respectively. Ethyl acetate and butanol extract of Medicago falcata completely inhibited Fusarium solani and Aspergillus fumigates, respectively. The n-hexane extract of Tecoma stan completely inhibited Fusarium solani, while its ethyl acetate extract shows excellent activity against Aspergillus niger.Conclusions: These findings provide scientific evidence of traditional use of medicinal plants and also indicate the potential of these plants for the development of antimicrobial agents.